Gaya Kepemimpinan Entrepreneur dalam Gereja Masa Kini - Josef Christianto; Michael Dendi Tinggogoy; Sendi Gunarto; Tony Tedjo; Yelmima Kadera (Sekolah Tinggi Teologi Sriwijaya, 2021)
Abstract: Church leaders are one of the main reasons that decide the church will be successful or not. Church leaders nowadays are requested to operate their leadership in such a way to answer every problems that happen on these days. One of the problems faced today is the lack of job opportunities as a result of the ongoing pandemic. The church as a social institution is asked to play an active role in helping to overcome this problem. Therefore we need a leadership style that is able to overcome these problems. In this paper, I will use a qualitative method by reviewing various literature sources to find a leadership style that fits the current context. Entrepreneur leadership style is one of many leadership styles that can be an option to solve any problems that churches are facing nowadays. Entrepreneur leadership style will create many jobs dan surely is going to solve this problems that happen during this pandemic Abstrak: Pemimpin gereja merupakan salah satu alasan utama yang menentukan berhasil atau tidaknya sebuah gereja. Pemimpin gereja masa kini diminta untuk menjalankan kepemimpinannya sedemikian rupa untuk menjawab setiap permasalahan yang ada saat ini. Salah satu permasalahan yang dihadapi saat ini adalah adalah minimnya ketersediaan lapangan pekerjaan sebagai dampak dari pandemi yang sedang terjadi. Gereja sebagai salah satu lembaga sosial diminta untuk berperan aktif membantu mengatasi hal tersebut. Oleh sebab itu diperlukan sebuah gaya kepemimpinan yang mampu mengatasi permasalahan tersebut. Dalam tulisan ini penulis akan menggunakan metode kualitatif dengan mengkaji berbagai sumber literature untuk menemukan gaya kepemimpinan yang sesuai dengan konteks masa kini. Gaya kepemimpinan entrepreneur adalah salah satu gaya kepemimpinan yang dapat dijadikan opsi untuk mengatasi berbagai macam permasalahan dalam gereja pada masa kini. Gaya kepemimpinan entrepreneur akan membuka lapangan pekerjaan baru dan tentu saja akan membantu menyelesaikan masalah yang sedang dihadapi di masa pandemi ini.